2023
DOI: 10.1111/evj.14029
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and obesity‐associated metabolic disease conditions in Connemara ponies in Ireland

Ahmed Saleh Al‐Ansari,
Emma Golding,
Nicola Walshe
et al.

Abstract: BackgroundEquine obesity combined with insulin dysregulation (ID) is a major risk factor associated with laminitis. Some pony breeds appear to be at increased risk. However, little is known regarding the prevalence of obesity or hyperinsulinaemia as evidence of ID in Irish ponies.ObjectiveTo investigate the prevalence of obesity and associated endocrine/metabolic disease conditions in Connemara ponies and to determine if hyperinsulinaemia in these ponies could be predicted by morphometric or metabolic markers.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…In this collection, two studies focused on equine obesity 19,20 . Obesity has been reported to be prevalent in many pony breeds and Al‐Ansari et al reported similar finding for Connemara ponies in Ireland 20 . Evidence of both regional and generalised obesity was reported in nearly 30% ponies, with the incidence of laminitis, or a history of laminitis being just under 50% in this specific population.…”
Section: Update On Obesitymentioning
confidence: 91%
See 1 more Smart Citation
“…In this collection, two studies focused on equine obesity 19,20 . Obesity has been reported to be prevalent in many pony breeds and Al‐Ansari et al reported similar finding for Connemara ponies in Ireland 20 . Evidence of both regional and generalised obesity was reported in nearly 30% ponies, with the incidence of laminitis, or a history of laminitis being just under 50% in this specific population.…”
Section: Update On Obesitymentioning
confidence: 91%
“…In this collection, two studies focused on equine obesity 19,20 . Obesity has been reported to be prevalent in many pony breeds and Al‐Ansari et al reported similar finding for Connemara ponies in Ireland 20 .…”
Section: Update On Obesitymentioning
confidence: 94%